Relationship between fruit growth and development and microstructural changes in six European plum varieties - YANG Fenfen; ZHANG Zhanhong; CAO Haiyang; WANG Yatong; GENG Wenjuan; FAN Guoquan; ZHANG Shikui (Guoshu xuebao)
[Objective] Reveal the phenological period, appearance, and the microstructure changes in different European plum varieties during fruit growth in order to understand the pattern of growth and development of European plum fruits and provide reference for improving fruit quality. [Methods] Six European plum varieties were selected as the experimental materials for tracing changes in fruit phenology, fruit appearance and cell microstructure at different developmental stages, which were analyzed by paraffin microtomy method. [Results] The whole fruit development could be divided into the first expansion period, the stone hardening period, the second expansion period, the color-changing period and the mature period. The fruit development period of the six European plum varieties was in the range of 121-160 d. Based on changes in fruit appearance, four stages could be distinguished: the rapid growth period (S1), the slow growth period (S2), the stable maturity period (S3) and the physiological fruit drop period (S4). Changes in fruit microstructure showed that the epidermis of the exocarp was a singlecell-layer structure, and the cell shape was neatly square and rectangular. Epidermis, subepidermis, mesocarp and vascular bundle cells in S1 were small, concentrated and dense. At S2, cells increased and diffused; at S3, the pericarp developed gradually; and the epidermis and mesocarp during S4 were relatively unchanged, while the subepidermis thickness became thinner and the phloem in the vascular bundle slightly degraded. Correlation analysis showed that there were significant correlations between fruit cell morphological parameters and appearance morphological indexes. [Conclusion] Revealed the pattern of fruit development and microstructure changes among six European plum varieties. It was found that the epidermis, subepidermis, mesocarp and vascular bundle cells expanded significantly in the early stage of fruit development, and tended to be stable in the late stages, accompanied by thinning of the subepidermis and slight degradation of phloem in the vascular bundle. The fruit appearance is closely related to the area, perimeter, longitudinal diameters, equatorial diameter and roundness of mesocarp cells, and the morphology of mesocarp cells also has a direct impact on the longitudinal diameters and equatorial diameter of the exocarp cells. In order to provide an important reference for the regulation of fruit development process related cultivation methods and effective prevention and control of fruit cracking hazards by observing fruit phenology and analyzing growth and development changes.